Atomic-scale investigations on the wet etching kinetics of Ge versus SiGe in acidic H2O2 solutions: a post operando synchrotron XPS analysis. Issue 29 (7th July 2020) - Abrenica, Graniel Harne A.; Lebedev, Mikhail V.; Fingerle, Mathias; Arnauts, Sophia; Bazzazian, Nazaninsadat; Calvet, Wolfram; Porret, Clement; Bender, Hugo; Mayer, Thomas; de Gendt, Stefan; van Dorp, Dennis H.
Abstract : In this atomic-scale study on wet etching, the importance of surface chemistry, in particular the nature of the surface oxides, is demonstrated for technologically relevant group IV semiconductors, Ge and SiGe. Abstract : In this atomic-scale study on wet etching, the importance of surface chemistry, in particular the nature of the surface oxides, is demonstrated for technologically relevant group IV semiconductors, Ge and SiGe. Elemental quantification of Ge in hydrochloric acid solution containing hydrogen peroxide showed a striking impact of the Si bulk concentration on the kinetics of etching. Post operando surface analysis provided insight into the oxide product formed after etching: a non-homogeneous porous layer with a depletion of Ge components at the outer surface due to pull out effects. Oxide formation was verified by microscopic imaging. We provide basic reaction schemes that help to elucidate the results.